Behavioral economics: the impact of news on investor sentiment in financial markets - Klenk, Jascha Camilo (2017)
This thesis analyses the extent of irrational human behaviour in the financial world, and the implications that these behaviours have on prices in financial markets as a whole. Because this research covers various fields, from general economic theory, over human cognition and group decision making to power of the media, we start out by explaining the link between these areas, by integrating individual and collective cognition into economic theory. Doing so, we show how an individual’s cognition is influenced by its peers and the surrounding, leading to group decision-making, a process in which individuals subordinate their own beliefs under the generalized belief of the group. In this regard a special focus will be put in analysing the effects that the media has in influencing the minds of the masses. We will then go on to investigate towards the effects that irrational investor behaviour has on the prices of believed to be efficient financial markets. In these introductory sections, this theses complements to behavioural, financial and economic literature by explaining the impact of individual cognition within these already established theories and explaining the role the media has in influencing collective cognition and therefore altering prices in financial markets. While most of recent research in cognitive science has focused on forming hypotheses and models of cognition and subjecting them to experimentation (Bourgine, 2004), this theses contributes to behavioural and financial research by testing the impacts of certain behaviour paradigms in the case of the United Airline Stock undervaluation in September 2008. Doing so, we empirically analyse the course of this undervaluation, the context in which it occurred and which cognitive phenomena might be responsible for the undervaluation. By means of textual analysis of media coverage regarding United Airlines throughout this episode we explain the influence of the media leading to this mispricing, and ultimately define excessively negative investor sentiment resulting from this media coverage to be the main reason for this undervaluation.